HUBUNGAN ANTARA MOTIVASI BELAJAR SISWA DAN PENAMPILAN GURU TERHADAP HASIL BELAJAR SISWA - Cahyadi, Rahman (JURNAL e-DuMath, 2016)
The one of technical element is the appearance of teachers teaching in the classroom teaching. The appearance of a good teacher will be able to create an effective learning environment and is able to manage the learning process. The appreance teachers teach are directly related to student motivation, that meaning if the appearance of teachers teaching in accordance with the expectations of students, then students will be motivated to study well. As the results of observations made, data showed the average value of the results of students mathematics learning in the material integers remained low at 55. This is shown still many students who scored less than standard KKM defined in MI Baiturahman Pugung mathematics courses that 60. The low learning achievement, presumably because learning is influenced by several factors, including internal factors such as student motivation, while external factors such as the appearance of teachers in teaching. From the research, that the appearance of teachers teaching and students motivation contributed 86.67% while the rest is determined by other factors. The amount of these contributions shows that the appearance of teachers teaching and students motivation to have a significant correlation with the results of students mathematics learning material especially integers.